Relationship between the molecular interaction and the structure of the bent core liquid crystals in the nematic phase - Jang, Yun (Trinity College (Dublin, Ireland). Department of Electronic & Electrical Engineering, 2012)
The relationship between the molecular interaction and the molecular structure of the bent core mesogens in the nematic phase is investigated in detail. Various physical phenomena are observed and interpreted.
Keywords: Electronic and Electrical Engineering, Ph.D.; Ph.D. Trinity College Dublin.